Stochastic Production Frontier Analysis and Technical Efficiency of Yellow Yam (Dioscorea cayenensis) Farmers in Orhiowmon Local Government Area of Edo State, Nigeria - Eweka, Kayode Israel; Egbodion, John; Osaherunwmen, Samuel (Direct Research Journal of Agriculture and Food Science, 2024)
Yellow yam has both socio-cultural and traditional values in the life of the people in Orhionmwon local government area. This study applied the stochastic production frontier analysis to measure the technical efficiency of yellow yam producers, the Cobb Douglas functional form was used to estimate the technical efficiency. Two-stage sampling technique was used in selecting (100) yellow yam farmers for the study. Primary data was collected directly from the field using structured questionnaire with open and close ended questions. Descriptive and inferential statistics was used for data analysis. The study showed majority of respondents constituting 69% of the population, were males. The SPF estimates reveals that yam setts and staking materials positively and significantly influenced the output of yellow yam production at (P<0.05) and (P<0.1) respectively. The mean technical efficiency of 55% showed that the farmers were operating below the frontier. Since the yield of yellow yam is increased by farm size, farmers in the study area should acquire more land for production and younger farmers should be encouraged to go into the production of yellow yam as the present producers are relatively too old for the labour intensive practices.